Alignment of new product development and product innovation strategies: a case study of Thai food and beverage SMEs. (2016) - Chaochotechuang, Preecha; Mariano, Stefania
This paper investigates the state of practice of product innovation management in the new product development (NPD) process in Thai food and beverage small and medium enterprises (SMEs). These SMEs play a major role in the Thai economy and yet little is known about their innovation management for NPD. Inspired by a relevant existing theoretical model, the current exploratory research collects data from 20 case organisations. Results reveal that: (1) top executives are mainly responsible for NPD projects; (2) barriers to developing products include lack of technology, financial resources, workforce's skills, and restrictive local laws; (3) to overcome these barriers and also to enhance their competitiveness, SMEs mainly adopt networking, resource-based, knowledge-based, open innovation, and technology buy/make strategies. We discuss these findings, provide implications for theory and practice, and suggest future research directions.